2019
DOI: 10.3390/ani9040119
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Insects as Feed: A Multi-Perspective Review

Abstract: Recently, insects have received increased attention as an important source of sustainable raw materials for animal feed, especially in fish, poultry, and swine. In particular, the most promising species are represented by the black soldier fly (Hermetia illucens, HI), the yellow mealworm (Tenebrio molitor, TM), and the common house fly (Musca domestica, MD). Although rapid development is expected, insects remain underutilized in the animal feed industry mainly due to technical, financial, and regulatory barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
214
0
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(229 citation statements)
references
References 64 publications
3
214
0
12
Order By: Relevance
“…Results of the logistic models showed that citizens’ attitude towards the use of insects to feed animals consistently explain citizens’ willingness-to-accept the use of insects to feed animals, regardless of the specie fed. These results are in line with previous literature that found that individuals holding more positive attitudes were more willing to accept new food technologies (Van huis, 2013; Verbeke et al, 2015; Vidigal et al, 2015; Hartmann et al, 2015; Sogari et al, 2019). Such result is important, because personal attitudes related to the use of insects to feed animals might outweigh the adverse impact of perceived uncertainty and perceived concern related to it (Verbeke et al, 2015).…”
Section: Discussion and Concluding Commentssupporting
confidence: 93%
See 1 more Smart Citation
“…Results of the logistic models showed that citizens’ attitude towards the use of insects to feed animals consistently explain citizens’ willingness-to-accept the use of insects to feed animals, regardless of the specie fed. These results are in line with previous literature that found that individuals holding more positive attitudes were more willing to accept new food technologies (Van huis, 2013; Verbeke et al, 2015; Vidigal et al, 2015; Hartmann et al, 2015; Sogari et al, 2019). Such result is important, because personal attitudes related to the use of insects to feed animals might outweigh the adverse impact of perceived uncertainty and perceived concern related to it (Verbeke et al, 2015).…”
Section: Discussion and Concluding Commentssupporting
confidence: 93%
“…Studies about consumer preferences and barriers for using insects to feed animals are scanty (Van Huis, 2013; Sogari et al, 2019). Verbeke et al (2015), in a research conducted in Belgium, investigated citizens’ acceptance of using insects in animal feed.…”
Section: Introductionmentioning
confidence: 99%
“…Feed vs Food -Some issues of neophobia exist when consumers are faced with the direct insect consumption (insects as food) (Sogari et al 2019a). However, they responded positively to the question if they would eat meat products from livestock fed insect meals (insects as feed), when properly informed about current animal feed issues (Verbeke et al 2015;Mancuso et al 2016;Ferrer Llagostera et al 2019;Macombe et al 2019;Sogari et al 2019b). Moreover, in this case, insect-based feeds and animal food from livestock fed with them are considered to have a better nutritional value and to be more sustainable than the conventional feed/food counterparts (Verbeke et al 2015;Ferrer Llagostera et al 2019).…”
Section: Opportunitiesmentioning
confidence: 99%
“…Legal framework -Under the current EU legislation framework, the short list of allowed substrates for mass rearing is a bottleneck for the development of the insect industry. In the EU, in the light of the 'precautionary' principle applied to the food safety policy, substrates such as catering or animal wastes are forbidden, even though in other parts of the world the scenario is quite different and sometimes with less restrictions in the use of wastes and other poor substrates (Pinotti et al 2019;Sogari et al 2019b;Fowles and Nansen 2020). The limitations imposed at EU scale have several implications because the available data on the environmental and economic sustainability of the insects as feedstuff indicate that insect meals are more sustainable when insects are grown on poor substrates, often not authorised in the EU (Bosch et al 2019;Smetana et al 2019).…”
Section: Threatmentioning
confidence: 99%
“…Worms such as superworms (Zophobas morio) and mealworms (Tenebro molitor) belongs to the darkling beetle (Tenebrionidae) family and are naturally voracious pests in agriculture, consuming dry grain stock even though they are food sources themselves in many societies 7 . Mealworms have been recently shown to be able to consume and metabolize plastics 8 safely, a capability attributed to commensal gut bacteria in these worms confirmed with 13 Ccarbon isotope tracing experiments 9 .…”
Section: Introductionmentioning
confidence: 99%